Phosphorus Cycling in the Red Tide Incubator Region of Monterey Bay in Response to Upwelling - Mackey, Katherine R.; Mioni, Cecile E.; Ryan, John P.; Paytan, Adina (Frontiers in Microbiology, 2012)
This study explores the cycling of phosphorus (P) in the euphotic zone following upwelling in northeastern Monterey Bay (the Red Tide Incubator region) of coastal California, with particular emphasis on how phytoplankton and bacteria mediate and respond to changes in P availability. In situ measurements of nutrient concentrations, phytoplankton community composition, and cell-specific alkaline phosphatase (AP) activity (determined via enzyme labeled fluorescence assay) were measured during 3 cruises. Upwelling led to a 10-fold increase in dissolved inorganic (DIP) in surface waters, reaching 0.5 mol L-1. This DIP was drawn down rapidly as upwelling relaxed over a period of 1 week. Relatively low ratios of nitrate to DIP uptake ( 5:1) suggest that luxury P uptake was occurring as phytoplankton bloomed. Dissolved organic (DOP) remained relatively constant ( 0.3mol L-1) before and immediately following upwelling, but doubled as upwelling relaxed, likely due to phytoplankton excretion and release during grazing. This transition from a relatively high DIP:DOP ratio to lower DIP:DOP ratio was accompanied by a decline in the abundance of diatoms, which had low AP activity, toward localized, spatially-heterogeneous blooms of dinoflagellates in the genera Prorocentrum, Ceratium, Dinophysis, Alexandrium, and Scrippsiella that showed high AP activity regardless of ambient DIP levels. A nutrient addition incubation experiment showed that phytoplankton growth was primarily limited by nitrate, followed by DIP and then DOP, suggesting that P is a regulating, rather than limiting, nutrient in this region. AP activity was observed in bacteria associated with lysed cell debris and aggregates of particulate organic material, where it may serve to facilitate P regeneration, as well as affixed to the surfaces of intact phytoplankton cells, possibly indicative of close, beneficial phytoplankton-bacteria interactions.